Photodynamic and Photothermal Therapy of Hepatocellular Carcinoma - Fan, Zhe; Zhuang, Chengjun; Wang, Shuang; Zhang, Yewei (Frontiers in Oncology, 2021)
Abstract Hepatocellular carcinoma (HCC) is the most common primary liver tumor. It is ranked the sixth most common neoplasm and the third most common cause of cancer mortality. At present, the most common treatment for HCC is surgery, but the 5-year recurrence rates are still high. Patients with early stage HCC with few nodules can be treated with resection or radiofrequency ablation (RFA); while for multinodular HCC, transarterial chemoembolization (TACE) has been the first-line treatment. In recent years, based on medical engineering cooperation, nanotechnology has been increasingly applied to the treatment of cancer. Photodynamic therapy and photothermal therapy are effective for cancer. This paper summarizes the latest progress of photodynamic therapy and photothermal therapy for HCC, with the aim of providing new ideas for the treatment of HCC.